A Nonlinear Model Predictive Control Strategy Using Multiple Neural Network Models. - Ahmad, Zainal; Jie, Zhang (2006)

(untitled)
Combining multiple neural networks appears to be a very promising approach for improving neural network generalization since it is very difficult, if not impossible, to develop a perfect single neural network.